Effective prevention of charge trapping in red phosphorus with nanosized CdS modification for superior photocatalysis. Issue 6 (December 2021) - Aihemaiti, Xiadiye; Wang, Xin; Wang, Zhuanhu; Bai, Yuexia; Qi, Kezhen; Ma, Yuhua; Tao, Kaixin; Simayi, Mayire; Kuerban, Nueramina
Abstract: The hydrothermal-treated red phosphorus (HRP) is a visible light response element semiconductor. However, photoelectrons and holes to recombine easily due to its narrow band gap. A CdS/HRP hierarchical heterostructure was designed. The CdS nanoparticle was uniformly dispersed on the surface of HRP, and the modification ameliorated the overgrowth, agglomeration and shortened the carrier migration distance of HRP, thereby significantly enhancing the photoreduction rate for Cr(VI). The strongest photocatalytic activity of the 1%CdS/HRP composite was obtained when the mass fraction of CdS was 1%. The reduction rate of Cr(VI) was 1.4 × 10 −1 min −1, which was 17.5 times that of HRP. After five cycles of photoreduction experiments, 1%CdS/HRP still possessed high photocatalytic activity (91.7%). The lower PL intensity of 1%CdS/HRP indicated the lower recombination rate of the photoelectrons and holes. The intensity of the transient photocurrent signal was significantly higher after the compounding of CdS and HRP, indicating the increase in the number and density of photogenerated carriers. A series of experimental results showed that the construction of heterojunction between CdS and HRP contributed to the intimate interfacial contact, which was beneficial for charge separation and transfer, and improved the photocatalytic performance of the catalyst. Highlights: Construction of CdS/HRP was beneficial for separation and transfer of photogenerated carriers. The strongest photoreduction rate of 1%CdS/HRP composite was 17.5 times higher than that of HRP. The potential photocatalytic Cr(VI) reduction mechanism of CdS/HRP was systematically explored.